Belonging and recognition after the post-election violence: a case study on labour migrants in Naivasha, Kenya - Lang, Britta; Sakdapolrak, Patrick (ERDKUNDE, 2014)
The 2013 general elections in Kenya entailed no recurrence of the 2007–08 post-election violence. Closer examination at the local level, though, indicates that the experiences of violence continue to influence the social sphere. Divisions between a long-established population and newcomers are blatant especially at places with high levels of immigration. This paper addresses how experiences of violent conflict over identitary and territorial belonging affect and transform socio-spatial organisation. The analysis is based on an empirical study at one of the venues of the post-election violence, a poor and heterogeneous workers’ settlement in Naivasha in Kenya’s Rift Valley. Naivasha area is internationally known for its horticultural production and massive labour immigration. After the 2007 elections, radical individuals of the local Kikuyu ethnic majority claimed Naivasha as their territory as a reaction to the displacement of Kikuyus from other parts of the country. Migrants of unwanted ethnic identity or political positioning were murdered or forcibly evicted from the place. Yet, due to poor job opportunities, especially in western Kenya, job seekers continue to migrate to Naivasha. The repercussions of the violence are expressed in the lack of acceptance, on the part of the long-established population at the place, of the presence of labour migrants. Experiences of ethnicised prejudice, mistrust, and fear between the self-described autochthonous population and labour migrants are tenacious. Kikuyus perceive Naivasha as their place of refuge and are willing to defend it if necessary. Migrants barely develop feelings of belonging to Naivasha, seeking rather to enhance their own security during their stay at the place. This study illustrates that memories of the violence still regulate socio-spatial realities and reinforce and accelerate processes of spatial and societal division.